1998
DOI: 10.1006/jesp.1997.1342
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Bias in Group Judgment Processes: The Role of Behavioral Memories

Abstract: Two experiments examined the role of memory for behavioral episodes in judgments about in-groups and out-groups. Using a minimal group paradigm, participants read either positive or negative trait-relevant behaviors performed by group members. They then were asked to make judgments about the group's trait characteristics. Results demonstrated that, for groups described positively, judgments about the out-group but not the in-group were accomplished by retrieving from memory specific behaviors performed by grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…In what follows we adopt the position that episodic and semantic memories are functionally independent. Episodic memories of a personal past clearly are a potential source of trait information about the self (e.g., Conway, 2005;Klein & Loftus, 1993a;Klein, Loftus, & Burton, 1989; as well as other persons, e.g., Babey, Queller, & Klein, 1998;Klein et al, 1992b;Sherman & Klein, 1994;Sherman, Klein, Laskey, & Wyer, 1998). It would be strange, however, if these were the only source of data about oneself.…”
Section: Evidence For the Functional Independence Of Episodic And Semmentioning
confidence: 96%
“…In what follows we adopt the position that episodic and semantic memories are functionally independent. Episodic memories of a personal past clearly are a potential source of trait information about the self (e.g., Conway, 2005;Klein & Loftus, 1993a;Klein, Loftus, & Burton, 1989; as well as other persons, e.g., Babey, Queller, & Klein, 1998;Klein et al, 1992b;Sherman & Klein, 1994;Sherman, Klein, Laskey, & Wyer, 1998). It would be strange, however, if these were the only source of data about oneself.…”
Section: Evidence For the Functional Independence Of Episodic And Semmentioning
confidence: 96%
“…This was not the case: When participants were asked to recall a specific behavioural incident in which they manifested a particular trait (recall task), those who had first made a self-descriptiveness judgement were no faster than those who had not (e.g., Klein & Loftus, 1990, 1993aKlein et al, 1989Klein et al, , 1992b). Yet the procedure used is known to be sensitive enough to detect episodic priming when it occurs (e.g., Babey, Queller, & Klein, 1998;Klein et al, 1992b;Sherman & Klein, 1994;Sherman, Klein, Laskey, & Wyer, 1998). (For experiments showing that this result obtains regardless of how ''central'' a trait is to one's self-concept, see, for example, Klein, Cosmides, Tooby, & Chance, 2001;Klein & Loftus, 1990, 1993aKlein et al, 1992b.…”
Section: Testing For Trait Summaries: the Priming Taskmentioning
confidence: 96%
“…We have also found evidence for these hypotheses in our own research. In two experiments, Sherman, Klein, Laskey, and Wyer (1998) showed that perceivers relied on episodic memory to differing degrees when they had learned stereotype-consistent and stereotype-inconsistent information about a target group. When the stimulus information confirmed participants' expectancies that in-groups would be positive and out-groups would be negative, judgments about the groups did not involve the activation of specific episodes.…”
Section: Mechanisms Of Stereotype Plasticitymentioning
confidence: 99%